An In/Del mutation in upstream regulatory region of MC1R gene associated with grey lethal disease in grey Shiraz sheep (Persian lamb) - BEHROOZINIA, S; SAFDARIAN, M; FARHADI, A; KHEDERZADEH, S (The Indian Journal of Animal Sciences, 2018)
In the present study, MC1R, which play an important role in normal pigmentation in Skeen and wool, was candidate to assess the lethal grey disease in Persian lamb. Blood samples (50) were collected randomly from grey Shiraz sheep, and DNA was extracted by salting out method. One of these samples showing the disease was assigned as control case. Two pairs of specific primers of P1MC1R and P2MC1R were designed to amplify two fragments from upstream regulatory region (URR) and coding sequence (CDS) of MC1R gene. After genotyping by SSCP technique, samples from each banding patterns were sequenced and analyzed using BioEdit and DNASIS MAX softwares. Comparing sequences from control (sick lamb) with healthy ones showed different haplotype in productsof each specific primer pairs. The multiple alignments revealed a 26 bp In/Del occurring at PCR product of P1MC1R gene in control case which was not observed in other studied lambs, and also 7 and 11 different positions were seen between sequence amplified by P1MC1R and P2MC1R primers, respectively. Further bioinformatics analysis showed that 26 bp insertion/deletion (In/Del) occurred in control case P1MC1R sequence caused deletion of gamma_IRE_CS and LBP_1_RS motifs from URR of control case. It seems this 26 bp In/Del mutation might have changed its expression and can be potential cause of grey lethal disease in studied sheep breed.